PERBANDINGAN SAR DAN SARQR PADA PEMODELAN INDEKS PEMBANGUNGAN MANUSIA DI JAWA TENGAH TAHUN 2022 - Hapsery, Alfisyahrina; Hermanto, Elvira Mustikawati Putri; Aprilia, Yohanita Uniyantri (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2023)
The Human Development Index (HDI) is one of the indicators created to measure the success of human quality of life. Central Java is one of the provinces that has experienced a significant increase in HDI in recent years. However, the rankings of its regencies/cities have not shown significant changes. This study aims to model the HDI in Central Java based on the factors that influence it. The data used for modeling the HDI are secondary data obtained from the Central Statistics Agency (BPS) of Central Java, encompassing 35 regencies/cities in Central Java. The analysis in this study employs spatial analysis, specifically Spatial Autoregressive (SAR). Given the potential spatial effects at certain quantiles of the independent variables, the appropriate analysis is Spatial Autoregressive Quantile Regression (SARQR), which combines the SAR method with quantile regression. The best model from the study results is the SAR model, with factors influencing the HDI in Central Java including Population Percentage, Labor Force Participation Rate, Crime Rate, and Average Non-Food Expenditure. The cities of Semarang, Salatiga, and Surakarta have the highest HDI values at each quantile, ranging from the 0.10 quantile to the 0.90 quantile.